2016
DOI: 10.1016/j.bjorl.2015.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of turbinoplasty surgery efficacy in patients with and without allergic rhinitis

Abstract: The efficacy of inferior turbinoplasty was confirmed not only for obstructive symptoms, but also for non-obstructive symptoms in patients with and without allergic rhinitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…This lack of correlation, again in accordance with the literature, pointed out that the AAR provides only a global assessment and does not consider the local details of the nasal air flow (i.e. the anterior regions of inferior meatus or nasal valve) that are often extremely significant from clinical and QoL standpoints 22 25 .…”
Section: Discussionsupporting
confidence: 76%
“…This lack of correlation, again in accordance with the literature, pointed out that the AAR provides only a global assessment and does not consider the local details of the nasal air flow (i.e. the anterior regions of inferior meatus or nasal valve) that are often extremely significant from clinical and QoL standpoints 22 25 .…”
Section: Discussionsupporting
confidence: 76%
“…Hypertrophy of the inferior turbinate is a common problem in nasal obstruction. There are reasons to perform an anterior inferior turbinoplasty, especially in not on conservative therapyresponsive hypertrophy (22,23) . There are a variety of operational techniques that are described in the current literature to reduce the volume of turbinates (1,3,7,8,(24)(25)(26) .…”
Section: Acoustic Rhinometrymentioning
confidence: 99%
“…These results are in agreement with one study who assessed the efficacy of inferior turbinoplasty in patients with nasal obstruction. They found that after 3 months post-operative, 94.7% of patients had good improvement in breathing, either grades IV or V. 7 One study studied the long-term outcomes in medial flap inferior turbinoplasty in patients with nasal obstruction. They found that the procedure improved obviously nasal obstruction degree (the outcome was 90.2%) and they concluded that medial flap inferior turbinoplasty provided consistent, robust results.…”
Section: Post-operative Follow-up (Outcomes)mentioning
confidence: 99%